2014
DOI: 10.1007/s10750-014-1991-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct or similar? Soft bottom polychaete diversity in Arctic and Antarctic glacial fjords

Abstract: The main aim of this study was to compare the polychaete communities in two similar polar areas: an Arctic fjord, Hornsund (Svalbard) and an Antarctic fjord, Ezcurra Inlet (South Shetlands). This is the first attempt to compare Arctic and Antarctic diversity based on fully comparable datasets. Forty van Veen grab samples were collected in each fjord: twenty replicates were taken in each of two fjord areas characterized by a different level of glacial disturbance-in the inner (glacial bay) and outer (fjord mout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 75 publications
0
4
1
Order By: Relevance
“…Previous research suggests that habitat heterogeneity determines benthic community assembly in polar regions (Wlodarska-Kowalczuk et al, 2007;Somerfield et al, 2009;Pabis et al, 2015). Albeit those contributions studied soft-bottom communities, they suggest that the assembly of polar benthic communities is actually independent of historical context and alpha and gamma diversities (Pabis et al, 2015). This apparent discrepancy between our and previous results probably stems from the fact that our sampling method, vacuum dredge, allowed us to obtain organisms occurring on both, rocks and sand below the rocks.…”
Section: Caveats and Future Directionscontrasting
confidence: 93%
See 1 more Smart Citation
“…Previous research suggests that habitat heterogeneity determines benthic community assembly in polar regions (Wlodarska-Kowalczuk et al, 2007;Somerfield et al, 2009;Pabis et al, 2015). Albeit those contributions studied soft-bottom communities, they suggest that the assembly of polar benthic communities is actually independent of historical context and alpha and gamma diversities (Pabis et al, 2015). This apparent discrepancy between our and previous results probably stems from the fact that our sampling method, vacuum dredge, allowed us to obtain organisms occurring on both, rocks and sand below the rocks.…”
Section: Caveats and Future Directionscontrasting
confidence: 93%
“…However, the observed variation in salinity and light penetration have been previously associated with significant responses of the physiology, morphology, and diversity of benthic species in YEND and FILD (Valdivia et al, 2020;Palacios et al, 2021). Previous research suggests that habitat heterogeneity determines benthic community assembly in polar regions (Wlodarska-Kowalczuk et al, 2007;Somerfield et al, 2009;Pabis et al, 2015). Albeit those contributions studied soft-bottom communities, they suggest that the assembly of polar benthic communities is actually independent of historical context and alpha and gamma diversities (Pabis et al, 2015).…”
Section: Caveats and Future Directionsmentioning
confidence: 99%
“…For example, using grab samples from Livingstone and Deception Island San Martín et al (2000) recovered 3700 specimens of polychaetes belonging to 89 species. Pabis and Sicinski (2012) collected grab samples at Admiralty Bay, South Shetlands and found 76 polychaete species in depths ranging from 200 to 500 m. Comparative analysis by Neal et al (2011) also showed Admiralty Bay to have a depressed diversity similar to that of species-poor Arctic shelves, although depending on a choice of comparative Arctic site, these results can vary (see Pabis et al 2015c). There are 162 species known polychaete species from Admiralty Bay based on summary of more than 30 years of research in this area (Sicinski et al 2010).…”
Section: Diversity Comparisons Within the Amundsen And Scotia Seasmentioning
confidence: 99%
“…Admiralty Bay is probably the most comprehensively studied site in the Southern Ocean , providing a large background knowledge on diversity of benthic communities with special reference to the polychaete fauna based on the material gathered 20-30 years ago when climate warming was not as strongly pronounced as in the present time (e.g., Sicinski 1986Sicinski , 2004Petti et al 2006;Pabis and Sicinski 2010a, b). A recent polychaete diversity comparison (Pabis et al 2014b) showed that the level of disturbance in Ezcurra Inlet is much lower than in the Arctic fjord Hornsund. On the other hand, it is much higher than in the more southern WAP fjords (Grange and Smith 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Biodiversity analysis of those data was used for the bipolar comparison between Ezcurra Inlet and Arctic fjord Hornsund (Pabis et al 2014b). It is the first study with emphasis on polychaete biomass on the species level in the areas affected by glacial sedimentation inflow.…”
Section: Introductionmentioning
confidence: 99%